Biology of Tendon Stem Cells and Tendon in Aging - Lui, Pauline Po Yee; Wong, Chi Ming (Frontiers in Genetics, 2020)
Both tendon injuries and tendinopathies, particularly rotator cuff tears, increase with tendon aging. Tendon stem cells play important roles in promoting tendon growth, maintenance and repair. Aged tendons show a decline in regenerative potential coupled with a loss of stem cell function. Recent studies draw attention to aging primarily a disorder of stem cells. The micro-environment (“niche”) where stem cells resided in vivo provides signals that direct them to metabolize, self-renew, differentiate, or remain quiescent. These signals include receptors and secreted soluble factors for cell-cell communication, extracellular matrix, oxidative stress and vascularity. Both intrinsic cellular deficits and aged niche, coupled with age-associated systemic changes of hormonal and metabolic signals can inhibit or alter the functions of tendon stem cells, resulting in reduced fitness of these primitive cells and hence more frequent injuries and poor outcomes of tendon repair. This review aims to summarize the biological changes of aged tendons. The biological changes of tendon stem cells in aging are reviewed after a systematic search of the PubMed. Relevant factors of stem cell aging including cell-intrinsic factors, changes of microenvironment, and age-associated systemic changes of hormonal and metabolic signals are examined, with findings related to tendon stem cells highlighted when literature is available. Future research directions on the aging mechanisms of tendon stem cells are discussed. Better understanding of the molecular mechanisms underlying the functional decline of aged tendon stem cells would provide insight for the rational design of rejuvenating therapies.